ХУДОЖНІЙ ТЕКСТ ЯК ЗАСІБ ФОРМУВАННЯ ПРОФЕСІЙНОЇ КОМПЕТЕНТНОСТІ МАЙБУТНЬОГО ХОРЕОГРАФА (Педагогіка вищої та середньої школи, 2009)
The article reveals features of the conqietenUal approach in vocational training choreographers in the higher school. The method of work with the art text, based an a combination of elements of the comparative. valuable and hermeneutic analysis is offered. The mechanism of decoding of the art text from positions the comptfenlial approach is revealed by the example of ballet "Coppelio".